The anti-adipogenic effect of vitexin is via ERK 1/2 MAPK signaling in 3T3-L1 adipocytes - Yu-Hsien Lee; Shih-Huang Yang; Shiow-Ling Chen; Ya-Fang Pan; Chia-Ming Liu; Meng-Wei Li; Shih‐Shen Chou; Ming-Yung Chou; Su-Chung Youn (International Journal of Phytomedicine, 2014)
Vitexin, identified as apigenin-8-C-D-glucopyranoside, a natural flavonoid compound found in certain herbs such as hawthorn herb. The aim of this study is to investigate the regulation of glycolysis underlying vitexin-induced anti-adipogenesis in 3T3-L1 adipocytes. Vitexin inhibited adipose accumulation, glucose consumption and triglyceride synthesis. The expression of ERK 1/2 MAPK greatly induced, whereas the expression of adipogenic markers Akt and peroxisome proliferator-activated receptor γ (PPARγ) diminished. ERK 1/2 MAPK inhibitor PD98059 (10 μM) significantly enhanced lipid accumulation, triglyceride synthesis and the expression of adipogenic markers. However, PD98059 had no effect on glucose consumption. In regulation of glycolysis, vitexin induced the expression of glycerol-3-phosphate dehydrogenase (GPDH) at higher dosage (50 and 100 μM) and without any effect on glucose-6-phosphate dehydrogenase (G6PDH) expression. PD98059 had an opposing effect that it significantly increased the expression of G6PDH, but decreased the expression of GPDH. Vitexin increased the lactic acid synthesis to about 3.8 folds in concentration dependent, whereas, PD98059 decreased the level of lactic acid in media to about 72% when compared with controls. Moreover, PD98059 abolished the anti-adipogenic effect of vitexin. Vitexin influence the expansion of adipose tissue through its ability to inhibit preadipocyte migration to about 80% via decreased the activity of active MMP-2. We demonstrated evidences for the first time that using of vitexin to against adipose accumulation, at least in part, was regulation of glycolysis via activation of ERK 1/2 MAPK signaling. Moreover, blockade pentose phosphate pathway may be a novel strategy for obesity prevention and therapy.